PWE-252 Trends in imaging and impact of diagnostic medical radiation in inflammatory bowel disease. (28th May 2012) - Chatu, S; Poullis, A; Holmes, R; Greenhalgh, R; Pollok, R
Abstract : Introduction: Increasing use of diagnostic imaging in inflammatory bowel disease has led to concerns about the malignant potential of ionising radiation in a cohort that is already predisposed to malignancy. The aim was to quantify radiation exposure in inflammatory bowel disease patients referred from primary care, determine predictors of high exposure and evaluate temporal changes in imaging at a single centre. Methods: Patients with a diagnosis of Crohn's disease (CD) or ulcerative colitis (UC) were prospectively recruited from clinic between January 2011 and June 2011. Demographic and clinical data were obtained by scrutinising medical records. The number and type of imaging procedures was obtained from the radiology database which was first set up in 1990, we only included those diagnosed after the database was initiated. The effective dose of radiation from each test was estimated from published standardised tables. Cumulative effective dose (CED) was calculated for each subject by summing the effective doses of radiation from diagnosis until end of study period which was June 2011. Cox regression analysis was performed to assess for factors associated with potentially harmful levels of ionising radiation defined as total CED >50 mSv. Results: The cohort included 415 patients. Median disease duration for Crohn's disease and ulcerative colitis was 8.3 and 7.7 years. Median total CED was 7.2 mSv (IQR 3.0–22.7) in Crohn's disease and 2.8 mSv (IQR 0.8–8.9) in ulcerative colitis patients. A total of 32 patients (8%) received a CED >50 mSv. Multivariate analysis revealed a history of IBD related surgery had a HR of 7.7. During the study period usage of abdominal CT increased by 350%. Conclusion: About 1 in 10 patients were exposed to potentially harmful levels of ionising radiation therefore strategies to reduce radiation exposure are needed. While there was an increased uptake of both MRI and small bowel ultrasound over the past 20 years use of CT also increased substantially. Competing interests: None declared.